Analysis of the preliminary results of GPS observation series at the Poltava Gravimetrical Observatory - Zalivadnyi, N.M.; Nekrasov, V.V.; Schliahovoi, V.V. (Кинематика и физика небесных тел, 2005)
The first results of researches of GPS observations in Poltava are submitted. Linear trend, annual, semi-annual terms as well as a number of additional terms are marked out on each coordinate. It is shown that the annual term considerably prevails above semi-annual one. Numerical values of parameters of these components are determined. Comparison of the obtained results with results of the similar researches at the Kyiv Station has been carried out.